Takut Ketinggalan Jadi Alasan Beli: Pengaruh FoMO, Content Marketing, dan Perceived Quality terhadap Keputusan Pembelian JennSkin di Bali - Roziana, Komang Cesie Agnestia; Parasari, Nyoman Sri Manik; Basmantra, Ida Nyoman; Tirtayani, I Gusti Ayu (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the influence of fear of missing out (FoMO), content marketing, and perceived quality, both partially and simultaneously, on purchasing decisions. The study sample consisted of 190 JennSkin consumers residing in Bali. Data analysis was conducted through a series of tests, including Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, F-Test, and t-Test. The results showed that the fear of missing out variable had a positive and significant effect on purchasing decisions, meaning that the higher a consumer's FoMO level, the more likely they were to make a purchase. Furthermore, content marketing also proved to have a positive and significant effect, where the more engaging and informative the content presented, the greater the consumer's likelihood of purchasing the product. Perceived quality was also found to have a positive and significant effect, indicating that the better consumers perceive JennSkin's product quality, the higher their purchasing decisions. Based on these findings, the researchers offer several recommendations for JennSkin management. The company is expected to create more attractive promotions that last longer to enhance consumer satisfaction. Furthermore, the presentation of information related to product quality needs to be more comprehensive, clear, and easy to understand. Innovations can also be made to packaging design to make it more visually appealing. During certain occasions, such as holidays, twin dates, or other special events, JennSkin can leverage these opportunities to run more intensive marketing campaigns to increase consumer purchasing decisions.